The Problem of Forming the Environmental Youth Consciousness - Bazueva K. I.; Gazizova N. V. (SHS Web of Conferences, 2023)
The younger generation, as an integral part of any society, is the future of our country. The living conditions of people completely depend on the preferences of young people. Therefore, the question of the values and orientations of modern youth is becoming increasingly important in order to preserve the ecological balance in nature. The solution of the environmental problem is impossible without the awareness of the importance of this problem by the younger generation. In order to accurately define the role and significance of ecological consciousness in overcoming modern global environmental problems, it is necessary to first determine what is meant by ecological consciousness.